Performing global citizenship: women NGO workers' negotiations of complicities in their work practices - de Jong, Sara (2010)
The practices of NGOs and development agencies located in the global North have been criticised for displaying (post-)colonial continuities. Concurrently, western feminism has been critiqued for assuming universality in the experiences of white western women. Hence there is a need for reflection on operating within and resisting of these power structures.